Financial Statement Ratio Analysis to Assess Financial Performance at PT Polychem Indonesia Tbk - Rahmah Hasanah; Fitri Mareta; Heliani (Future Science, 2020)
The purpose of this study is to determine the financial performance of PT. Poly-chem Indonesia Tbk using financial ratio analysis from 2017 to 2019. The finan-cial ratios analyzed are Current Ratio (CR), Quick Ratio (QR), Debt Ratio (DR), Debt to Equity Ratio (DER), Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Investment (ROI) and Return on Equity (ROE). The data in this study uses data in the 2017-2019 financial statements. The data analysis meth-od used is the horizontal analysis method, which is useful for comparing financial reports in certain years. From the data analysis, it can be seen that the liquidity ratio of PT. Polychem Indonesia Tbk seen from the average CR and QR in the last 3 years was 336.5% and 184.1%. This proves that the current ratio and a quick ratio of PT. Polychem Indonesia Tbk is in good condition. The solvency ratio of PT. Polychem Indonesia Tbk is seen from the average DR and DER of PT. Polychem Indonesia Tbk in the last 3 years amounted to 22.6% and 33.1%. This condition shows the debt ratio and debt to equity ratio of PT. Polychem In-donesia Tbk is in good condition. Profitability ratio of PT. Polychem Indonesia Tbk seen from the Average Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Investment (ROI) and Return on Equity (ROE) in the last 3 years each was 0.0%, -5,3%, -4.8% and -6.1% are in poor condition because they are below the industry standard.